2021
DOI: 10.5194/egusphere-egu21-175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal and Mesoscale Variability of the Two Atlantic Water Recirculation Pathways in Fram Strait

Abstract: <p>Atlantic Water, which is transported northward by the West Spitsbergen Current, partly recirculates (i.e. turns westward) in Fram Strait. This determines how much heat and salt reaches the Arctic Ocean, and how much joins the East Greenland Current on its southward path. We describe the Atlantic Water recirculation's location, seasonality, and mesoscale variability by analyzing the first observations from moored instruments at five latitudes in central Fram Strait, spanning a period from Augus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Model suggests that the maximum in 2013/2014 can be attributed to a smaller recirculation back to Fram Strait (thus more flow through the YPB) and minima in 2015/2016 and 2017/2018 to a larger recirculation (thus less flow through the YPB; Athanase et al., 2021; their Figure 5). PSY4 was consistent with recent moorings on the prime meridian which also indicated that AW recirculations showed a maximum at 80°N in winter 2017 (Hofmann et al., 2021).…”
Section: Ypb In Mercator‐ocean Operational Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…Model suggests that the maximum in 2013/2014 can be attributed to a smaller recirculation back to Fram Strait (thus more flow through the YPB) and minima in 2015/2016 and 2017/2018 to a larger recirculation (thus less flow through the YPB; Athanase et al., 2021; their Figure 5). PSY4 was consistent with recent moorings on the prime meridian which also indicated that AW recirculations showed a maximum at 80°N in winter 2017 (Hofmann et al., 2021).…”
Section: Ypb In Mercator‐ocean Operational Modelsupporting
confidence: 85%
“…Interannual variations were important (Figure 13) likely due to the variable partitioning of the AW inflow between recirculations toward Fram Strait and branches over the Plateau (Figure 1b). For instance, the striking AW transport minimum in the YPB in 2017–2018 (Figure 13 and Figure S3 in Supporting Information ) corresponded to larger recirculations recorded in Fram Strait at 80.2°N, 0°E (Hofmann et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A significant fraction of the heat extracted from the branches of the NwAC to the interior of the Lofoten Basin is thought to be transported by mesoscale eddies, especially at the Lofoten Islands where eddies are the most intensively generated (Chafik et al., 2015; Isachsen, 2015; Kohl, 2007; Raj et al., 2020). Eddies also play an important role further north, where one of the westward recirculations of the AW in the Fram Strait is considered to be eddy‐driven (Boyd & D’Asaro, 1994; Hattermann et al., 2016; Hofmann et al., 2021; Nilsen et al., 2006; von Appen et al., 2015). However, except for some model studies (see, e.g., Hattermann et al., 2016; Spall et al., 2021; Treguier et al., 2021; Wekerle et al., 2020), the effect of coherent eddies on heat redistribution in these areas has not been evaluated and forms the core of this study.…”
Section: Eddies In the Nordic Seas From Satellite Altimetrymentioning
confidence: 99%
“…The EGC accounts for the export of ~50% of freshwater and ~90% of sea-ice from the central Arctic Ocean and carries Arctic hydrographic signatures 18 . Large-scale recirculation of Atlantic water (AW) into the EGC by eddies is a continuously occurring process, although the magnitude varies across latitudes and over temporal scales 19,20 . The mixing of these water masses in the marginal ice zone (MIZ) creates different hydrographic regimes reflective of Arctic, mixed water and Atlantic conditions, which can harbour unique bacterial compositions 21,22 .…”
Section: Introductionmentioning
confidence: 99%